36 - IMPROVEMENT OF THE FUNCTIONALITY AND OF THE QUALITY OF LIFE AFTER THE APPLICATION OF THE CONSTRAINT INDUCED MOVEMENT THERAPY (CIMT) IN A HEMIPARETIC PATIENT (Fiep Bulletin - online, 2011)
The therapy induced by contension is a technique that has been used very successfully in the rehabilitation of paretic superior member with encephalic vascular accident. This study's target is evaluating the improvement in life quality of hemiparetic patients treated by the therapy induced by contension. A study was made in a 53 year old, female patient who had left hemiparesy.The patient received the adapted protocol of the therapy, that lasts 2 weeks, at first for 1 daily hour and then for 3 daily hours of functional exercises involving the paretic superior member ,while the other healthy member was kept immobilized. To the evaluation of life quality the questionary SF-36 was used and to functionality, Barthel's index was used before and after the end of the therapy. In the statistical analysis the test T-student was used with significance level of 0.05 and 0.1.The results showed, through statistical analysis of life quality after one hour of therapy, a significance leved of 0.1 with a t-table of 1.90 and t-calculated 2.12 with 7 degrees of freedom. A after the 3 hour intervention, the t-calculated was 0.31 when compared to the 1 hour data, when analyzing the data before the 1 hour therapy with the data after 3 hours, a t-calculated of 2.15 was observed. In functionality after 1 hour of therapy, a score of 95 was observed and after 3 hours this score was the same. Based on it, this study concluded that there's improvement in the functional dependence amid in life quality of hemiparectic patients after the usage of Therapy Induced by Contension.
Keywords: Therapy Induced by Contension; Encephalic vascular accident